Peran Bumdes dalam Meningkatkan Perekonomian Masyarakat Melalui Sektor Pertanian di Desa Bangun Kecamatan Parbuluan Kabupaten Dairi - Capah, Silvanus Avan; Lubis, Yurial Arief (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This study aims to analyze the role of Baja Village-Owned Enterprises (BUMDes) in improving the community's economy through the agricultural sector in Bangun Village, Parbuluan District, Dairi Regency. The research method used is a qualitative approach with data collection techniques in the form of literature studies, observations, in-depth interviews, and documentation. The informants in this study consisted of eight people who were directly involved in the management of BUMDes. The results of the study show that Baja BUMDes play a role in providing business capital for farmers, improving labor skills through training programs, and providing more affordable production facilities. However, several factors hinder the optimization of the role of BUMDes, including limited capital, low use of technology, lack of community participation in training, lack of synergy with the government, and the impact of climate change. Therefore, cooperation between BUMDes, local governments, and the community is needed to strengthen sustainable agriculture-based economic development strategies.